1988
DOI: 10.1111/j.1365-2133.1988.tb03473.x
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind comparison of a dithranol and steroid mixture with a conventional dithranol regimen for chronic psoriasis

Abstract: Twenty four of 30 patients with chronic plaque psoriasis completed a double-blind randomized paired comparison of dithranol in Lassar's paste versus dithranol and fluocinonide in Lassar's paste. There was a more rapid reduction in severity of the psoriasis on the side treated with the dithranol and fluocinonide mixture, but no difference in the final time to clearance between the two sides. There were fewer burning episodes on the side treated with dithranol and fluocinonide and greater staining of the skin. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 3 publications
0
9
0
1
Order By: Relevance
“…No perilesional erythema was reported. Two other papers concluded that the combination of dithranol with a mid‐potent 47 or with a potent corticosteroid 46 respectively showed no significant differences compared to dithranol monotherapy. In the latter open clinical study 46 dithranol monotherapy was compared to combination therapy of dithranol with mometasone and to a combination regimen with dithranol and calcipotriol ointment.…”
Section: Resultsmentioning
confidence: 99%
“…No perilesional erythema was reported. Two other papers concluded that the combination of dithranol with a mid‐potent 47 or with a potent corticosteroid 46 respectively showed no significant differences compared to dithranol monotherapy. In the latter open clinical study 46 dithranol monotherapy was compared to combination therapy of dithranol with mometasone and to a combination regimen with dithranol and calcipotriol ointment.…”
Section: Resultsmentioning
confidence: 99%
“…Eine andere Arbeitsgruppe [7] berichtete allerdings während eines Nachbeobachtungszeitraums von 3 Monaten über höhere Rezidivraten bei einem mit einer Fluocinolon-Dithranol-Kombination behandelten Psoriasiskollektiv im ten die Therapie wegen periläsionaler toxischer Dermatitiden unterbrechen.…”
Section: Introductionunclassified
“…Grattan et al . noted a faster improvement early during treatment, while the total treatment period was equal in patients treated with dithranol only or with dithranol combined with a corticosteroid 14 . Runne and Kunze did not observe a better therapeutic result with the combination of dithranol and corticosteroids 15 .…”
Section: Discussionmentioning
confidence: 91%
“…13 Grattan et al noted a faster improvement early during treatment, while the total treatment period was equal in patients treated with dithranol only or with dithranol combined with a corticosteroid. 14 Runne and Kunze did not observe a better therapeutic result with the combination of dithranol and corticosteroids. 15 Mahrle and Schulze demonstrated that pretreatment with topical corticosteroids for 1 week reduced the response to dithranol and the duration of remission.…”
Section: Discussionmentioning
confidence: 91%